Documentation Analysis And Design Of Pospay Deployment Recapitulation System (Case Study: Pt. Pos Indonesia) - Pertiwi, Restu Putri; Mariatussadiah, Revanya Deriana; Permatasari, Intan; Kasenda, Yeru Pratama (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to improve the existing system, which at this time PT. Pos Indonesia, especially in the Pospay division, has not been able to fulfill information needs optimally, especially in the service deployment recapitulation process, staff must process data using Microsoft Excel and not use a well-integrated information system, there is no system that has a large storage for storing documents - Minutes of handover system (BAST) documents and the absence of a system that can facilitate employees in the process of recapitulation and search for data deployment for Pospay services. The methodology used in the Analysis and Design of Information System Recapitulation System Deployment of PT. Pos Indonesia is a Prototype methodology. The initial stage begins with an analysis using BPMN to describe the ongoing business processes. This information system design stage uses the Unified Modeling Language (UML) modeling language. This system is built based on web that can be accessed by parties related to the process. This study produces an Analysis and Design document that can be used by companies to develop information systems for recapitulation data deployment service recapitulation. This information system can manage user data, manage service deployment recapitulation data and manage BAST documents.